The Meat Paradox: Investigating Cognitive Dissonance and Strategies to Oppose It - Romein, Christophe (Student Undergraduate Research E-journal!, 2019)
The conflict between the belief that eating meat holds harmful effects, and the actual behaviour of eating meat, can lead to cognitive dissonance. The present study aims to investigate the dynamics of this dissonance, and ways to oppose it. To test whether omnivores experience cognitive dissonance, participants filled out an Animal Care Scale and an Animal Consumption Scale. A Pearson R correlational analysis was used to determine whether cognitive dissonance was present. There was no significant correlation between the ACaS and the ACoS. The differences between groups were however significant. Furthermore, several strategies to oppose cognitive dissonance have been identified.